Mekaniserad plantering med Eco-Planter i södra Sverige - Sigurdh, Mattias (SLU/Dept. of Forest Products, 2004)
This report is a thesis work for a B.Sc. in Forestry exam at the 5028, SLU. The work was an assignment from Södra Skogsägarna and the aim of the work was to investigate the economical and biological output after mechanical planting with Eco-Planter compared with traditional manual planting. Eco-Planter is a tool for mechanized planting, fixed at the end of the boom on a conventional harvester.